(3hUhd GdCNjGQ Edi CUhd GdCNHGQs - (3MSjf Hf YHO GdUeO Hf eMeO GdLHYj (B((3HVe aaJM(B) (3GdYGedj GdMGQKj GdgeOGfqj,J (B984 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd abjQ QHg GdZfi MSjf Hf YHO GdUeO GdMGQKi GdgeOGfi deG cGf GdJfbjg ai ReGffG gPG hGLHkG Ydi cd Gdecdajf hHg JMUjd GdSYGOI ai GdOfjG hGdOjf s
(3BNQgG (B:s
(3heKd cJGHg Cda HYO hGh GdLeY hbO jdMbhfg CjVkG HYO GdhGh hGdMeO ddg ChdkG hBNQkG hXGgQkG hHGWfkG hUdi Gddg Ydi SjOfG eMeO hBdg GdWjHjf GdWGgQjf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B17s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdeQcRjI (B_ (3EjQGf (B(1/1044) s
Keywords: (3GdMOjK h GdeUWdMs